The Effect of Alginate Concentration and 8 kHz Audiosonic Treatment on the Viability of Arbuscular Mycorrhizal Fungi in Biochar Pellets - Salsabila Salsabila; Anne Nurbaity; Vira Kusuma Dewi; Betty Natalie Fitriatin; Pujawati Suryatmana; Mieke Rochimi Setiawati (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2026)
The effectiveness of arbuscular mycorrhizal fungi (AMF) as a biofertilizer in enhancing plant growth is influenced by environmental factors that can inhibit germination and reduce spore viability. Encapsulation using alginate as a coating material, combined with audiosonic stimulation, may improve spore protection and physiological activity. This study was conducted from October 2025 to February 2026 at the Soil Biology Laboratory, Department of Soil Science and Land Resources, Faculty of Agriculture, Universitas Padjadjaran, to evaluate the interaction between alginate concentration and audiosonic treatment on AMF spore germination and viability. The experiment was conducted using a Completely Randomized Design (CRD) with six treatments and three replicates. Alginate concentrations consisted of 1%, 2%, and 3%, while the audiosonic treatments included no audiosonic exposure and exposure to 8 kHz at a duration of 8 hours per day. The results showed a significant interaction between alginate concentration and audiosonic treatment on AMF viability. The 2% alginate concentration resulted in the greatest spore viability. Keywords: Audiosonic, Alginate encapsulated, Arbuscula Mycorrhizal Fungi (AMF), Biochar pellets